Chromosome-based survey sequencing reveals the genome organization of wild wheat progenitor Triticum dicoccoides - Akpinar, Bala Ani; Biyiklioglu, Sezgi; Alptekin, Burcu; Havránková, Miroslava; Vrána, Jan; Doležel, Jaroslav; Distelfeld, Assaf; Hernandez, Pilar; IWGSC; Budak, Hikmet (Plant biotechnology journal, 2018)
Wild emmer wheat (Triticum turgidum ssp. dicoccoides) is the progenitor of wheat. We performed chromosome-based survey sequencing of the 14 chromosomes, examining repetitive sequences, protein-coding genes, miRNA/target pairs and tRNA genes, as well as syntenic relationships with related grasses. We found considerable differences in the content and distribution of repetitive sequences between the A and B subgenomes. The gene contents of individual chromosomes varied widely, not necessarily correlating with chromosome size. We catalogued candidate agronomically important loci, along with new alleles and flanking sequences that can be used to design exome sequencing. Syntenic relationships and virtual gene orders revealed several small-scale evolutionary rearrangements, in addition to providing evidence for the 4AL-5AL-7BS translocation in wild emmer wheat. Chromosome-based sequence assemblies contained five novel miRNA families, among 59 families putatively encoded in the entire genome which provide insight into the domestication of wheat and an overview of the genome content and organization.
Keywords: Genetic Loci; Triticum; Repetitive Sequences, Nucleic Acid; comparative genomics; tetraploidie; průtoková cytometrie; RNA, Untranslated; Genome, Plant; High-Throughput Nucleotide Sequencing; polyploidie; Chromosomes, Plant; Polyploidy; next-generation sequencing; Flow Cytometry; chromozomy rostlin; Genes, Plant; repetitivní sekvence nukleových kyselin; nekódující RNA; Poaceae; Tetraploidy; rostlinné geny; hexaploid wheat; wild emmer wheat; konzervovaná sekvence; vysoce účinné nukleotidové sekvenování; lipnicovité; mikro RNA; MicroRNAs; pšenice; genetické lokusy; genom rostlinný; Conserved Sequence; chromosome sorting